Islamic letter of credit (LC): An overview on legal and shari'ah issues - Che Hashim, R.; Abdul Aziz, A.Z. (2009)
Letter of credit serves as an instrument of payment in international trade. Its aim is to facilitate trade between seller and buyer from different countries. The Islamic banking flourishing environment promotes the use of Islamic LC as a method of financing in international trade particularly to Muslims and to the general public as a whole. Nowadays, this facility is offered not only by Islamic bank but also by some conventional banks. Both conventional and Islamic LCs are governed by the same rules of the UCP 600 which is originally western and drafted by western people. Realizing the bizarre in the application of this conventional rule to Islamic LC, this paper focuses on the aim of harmonizing the practice of Islamic LC with the requirement of Shariah principles where elements such as interest (riba) and uncertainties (gharar) are prohibited. It begins by giving a background of Islamic LC in Malaysia. Next, it discusses the definition and types of Islamic LC which consists of al-murabahah, al-wakalah and al-musharakah as the issuance of Islamic LC is based on these three concepts. In addition, it highlights comparisons between these three concepts. Furthermore, the focal point of discussion is on Shariah issues in the practice of Islamic LC, such as governing rule, subject-matter, interest, insurance , aqad, discrepancy fee, and risk of goods in Islamic LC. Discussion on those issues identified whether they are in compliance with Shariah principles. In relation to this, various proposals are suggested to harmonize the rules applicable to Islamic LC and Shariah principles.